2022
DOI: 10.1002/hsr2.1009
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a meta‐analysis on orthopaedic surgeons' practice with regards to vancomycin graft pre‐soaking in anterior cruciate ligament reconstruction: A paper questionnaire survey study

Abstract: Background and Aims Understanding the impact of orthopaedic scientific research is vital in identifying facilitators and barriers to its implementation in clinical practice. A meta‐analysis was carried out which showed that presoaking hamstring (HT) autografts in vancomycin was associated with a 10‐fold reduction in infection rate in anterior cruciate ligament (ACL) reconstruction. Our aim was to determine the practice of orthopaedic surgeons with regards to vancomycin presoaking and explore wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…A survey of members of the ACL study group reported that about one-third (38%) of respondents presoaked their ACL grafts in vancomycin and that the major barrier to vancomycin presoaking related to concerns about potential detrimental effects on the mechanical properties of the graft 3 . Similar concerns were also raised by a questionnaire study that evaluated the impact of a meta-analysis assessing the relation between vancomycin presoaking and infection rates 24 .…”
Section: Discussionmentioning
confidence: 85%
“…A survey of members of the ACL study group reported that about one-third (38%) of respondents presoaked their ACL grafts in vancomycin and that the major barrier to vancomycin presoaking related to concerns about potential detrimental effects on the mechanical properties of the graft 3 . Similar concerns were also raised by a questionnaire study that evaluated the impact of a meta-analysis assessing the relation between vancomycin presoaking and infection rates 24 .…”
Section: Discussionmentioning
confidence: 85%